Educação Tutorial como ferramenta no Ensino-Aprendizagem de Audiovisual - Magnoni, Antonio Francisco [UNESP]; Miranda, Giovani Vieira (My University, 2012)
This paper aims to highlight the importance of Tutorial Education Program (TEP) for undergraduate courses in conjunction with the graduate programs, highlighting the relevance of the triad teaching, research and extension activities also present in the TEP Interdisciplinary in Radio and Television from the FAAC/UNESP.

Este trabajo tiene como objetivo destacar la importancia del Programa de Educación Tutorial (PET) para cursos de pregrado en conjunto con los programas de postgrado, destacando la importancia de la triade enseñanza, investigación y extensión también presentes en el PET Interdisciplinario en Radio y Televisión FAAC/ UNESP.

O presente trabalho objetiva destacar a importância de um Programa de Educação Tutorial (PET) para os cursos de graduação, em articulação com os programas de pós-graduação, destacando a relevância da tríade ensino, pesquisa e extensão também presentes no PET Interdisciplinar em Rádio e Televisão da FAAC/UNESP.
Tutorial education as tool of audiovisual teaching-learning
Educación tutorial como herramienta de enseñanza-aprendizaje audiovisual
Keywords: Audiovisual communication; Tutorial education; Radio And Television; Comunicación audiovisual; Educación tutorial; Radio y Televisión; Comunicação audiovisual; Educação tutorial; Rádio e Televisão